Pengetahuan Masyarakat Tentang Asam Jawa Untuk Menyembuhkan Batuk - Susilo Yulianto (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Knowledge Society, Tamarind, Cough Cure. Cough is one of the body's defense mechanisms, especially respiratory should be managed properly. Cough mechanism depends on five components: cough receptors, afferent nerve center, cough, nerve efferent, and effector. The purpose of this study was to determine the public's knowledge about the tamarind to cure cough. This research is descriptive quantitative research with cross sectional approach. Technique intake of study subjects using quota sampling of 30 samples. Data was analyzed by descriptive analysis. Results of analysis of the data showed that respondents who have a good knowledge of a number of 27 respondents (90%), while respondents who have sufficient knowledge of three respondents (10%).